2018
DOI: 10.1177/1049731518772142
|View full text |Cite
|
Sign up to set email alerts
|

A Nonrandomized Controlled Trial of Strengths Model Case Management in Hong Kong

Abstract: This study evaluates the effectiveness of the strengths model of case management (SMCM) for people with severe mental illness in Hong Kong. This is the first controlled trial outside the United States to investigate the impacts of SMCM on caseworkers as well as service users alongside fidelity measures. Method: Service users and their caseworkers were recruited from three types of supported accommodation for this 12-month nonrandomized controlled trial. Mixed modeling was used to investigate within-subject dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 62 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…Redko et al ( 2007 ) also found that people with substance abuse issues receiving SMCM highlighted goals as an important focus of the client-case manager relationship. In Tsoi et al’s ( 2019 ) SMCM study, one of the only differences between their SMCM group and a comparison group (case management without SMCM) was higher goal achievement of the SMCM group. Movement on practical goals is identified as a key element in building the alliance and fostering hope in both community mental health literature (Farrelly & Lester, 2014 ; Kidd et al, 2017 ; Redko et al, 2007 ; Tsoi et al, 2019 ) and psychotherapy research (Baldwin et al, 2007 ; Fluckiger et al, 2018 ; Wampold, 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…Redko et al ( 2007 ) also found that people with substance abuse issues receiving SMCM highlighted goals as an important focus of the client-case manager relationship. In Tsoi et al’s ( 2019 ) SMCM study, one of the only differences between their SMCM group and a comparison group (case management without SMCM) was higher goal achievement of the SMCM group. Movement on practical goals is identified as a key element in building the alliance and fostering hope in both community mental health literature (Farrelly & Lester, 2014 ; Kidd et al, 2017 ; Redko et al, 2007 ; Tsoi et al, 2019 ) and psychotherapy research (Baldwin et al, 2007 ; Fluckiger et al, 2018 ; Wampold, 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…There may be parallels with efforts to integrate strengths-based approaches into mental health care. Strengths-based approaches have a strong evidence base (Tse et al, 2016) and are now being evaluated in Hong Kong (Tsoi et al, 2019;Tse et al, 2019). Another resource available in Hong Kong are peer support workers (Tse et al, 2017), and their role in supporting well-being merits future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature (including the SMCM-specific studies) supports the effectiveness of generic strengths-based case management in improving client outcomes, such as reducing hospitalization, improving physical and mental health, increasing employment, and increasing social support and satisfaction with life [1,[9][10][11][12][13][14][15][16][17]. Aside from client outcomes, Tsoi and colleagues [18] found that the SMCM was effective for reducing emotional exhaustion among case workers.…”
Section: Introductionmentioning
confidence: 99%